2020
DOI: 10.1016/j.jagp.2020.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of American Older Adults with Pre-existing Depression During the Beginnings of the COVID-19 Pandemic: A Multicity, Mixed-Methods Study

Abstract: To determine the effect of the COVID-19 pandemic on the mental health of older adults with pre-existing major depressive disorder (MDD). Participants: Participants were 73 community-living older adults with pre-existing MDD (mean age 69 [SD 6]) in Los Angeles, New York, Pittsburgh, and St Louis. Design and Measurements: During the first 2 months of the pandemic, the authors interviewed participants with a semistructured qualitative interview evaluating access to care, mental health, quality of life, and coping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
154
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(178 citation statements)
references
References 14 publications
(12 reference statements)
12
154
2
2
Order By: Relevance
“…It illustrates, however, that suicide rates will not increase immediately, but possibly only with a time lag. This is consistent with studies reporting no increase in suicidal behaviour, used as an indirect measure for suicide risk, in the early stages of the COVID-19 pandemic [31][32][33][34][35][36][37] .…”
Section: Discussionsupporting
confidence: 90%
“…It illustrates, however, that suicide rates will not increase immediately, but possibly only with a time lag. This is consistent with studies reporting no increase in suicidal behaviour, used as an indirect measure for suicide risk, in the early stages of the COVID-19 pandemic [31][32][33][34][35][36][37] .…”
Section: Discussionsupporting
confidence: 90%
“…Our study found overall declines in loneliness over time that is consistent with other surveys of older adults finding resilience to psychological distress during COVID‐19 29,30 . Important differences in the severity of loneliness over time and an ability to adapt were found among study participants that highlights the importance of understanding nuances of individual experiences of loneliness.…”
Section: Discussionsupporting
confidence: 88%
“…Among individuals who experienced loneliness that worsened or remained severe over time, common themes from open‐ended feedback included an inability to cope emotionally, insufficient social support, and inadequate access or comfort with technologies for social interaction. In contrast, individuals who experienced no negative impact of the pandemic on loneliness reported the successful use of technology, positive emotional coping, and an ability to use city services (including senior center outreach, volunteer organizations, and services like Meals on Wheels) that is consistent with experiences in other parts of the country 30 . Notably, a minority of participants reported no difference in their loneliness during the pandemic because of already being isolated due to prior medical conditions (e.g., blindness, bedbound).…”
Section: Discussionmentioning
confidence: 75%
“…A similar survey in 932 adults in the UK reported that self-isolating/social distancing females, younger age groups, those with a lower annual income, current smokers, and those with physical multimorbidity showed higher levels of poor mental health [10]. In contrast, a qualitative US study among 73 older adults with pre-existing depression reported a surprisingly high resilience among this group within the first 2 months of the COVID 19 pandemic, with participants being more concerned about the risks of contracting the virus than the risks of isolation [11].…”
Section: Psychological Impact Of Covid-19 On the General Populationmentioning
confidence: 92%